Comparative Study of Nitrogen Cycling Between a Bay With Riverine Input and a Bay Without Riverine Input, Inferred From Stable Isotopes - Chen, Chunqing; Lao, Qibin; Shen, Youli; Jin, Guangzhe; Chen, Fajin; Su, Qizhong; Lei, Xuetie; Zhou, Xin; Lu, Xuan; Zhu, Qingmei; Liu, Guoqiang (Frontiers in Marine Science, 2022)
The eutrophication degree in the coastal bay has been increasing significantly for the past years, due to the increasing nutrient discharge. However, the factors controlling sources and nitrogen (N) cycling in the different types of bays are still poorly understood. In this comparative study, nitrate dual isotopes (δ15N−NO3− and δ18O−NO3−) and ammonium nitrogen isotope (δ15N−NH4+), were used to determine the origin of nitrate in Qinzhou Bay (with riverine input) and Tieshangang Bay (without riverine input) in Beibu Gulf and to study biogeochemical processes associated with nitrogen cycling. The nutrient concentrations generally showed a decreased trend from the upper bay to the outer bay. The isotopic values in Tieshangang Bay were generally higher than that in the Qinzhou Bay, suggesting that there are differences in nitrate sources and transformation processes between the two bays. The dominant sources from manure and sewage (41%) and soil N (30%) from runoff input were responsible for the high nitrate observed in the upper Qinzhou Bay. Though manure and sewage (59%) were also dominant nitrate sources in the upper Tieshangang Bay, a decrease in source from soil N (20%) occurred due to less runoff input. Nutrients were retained in the upper Tieshangang Bay due to weak hydrodynamic conditions, which caused higher NH4+ concentrations in the upper bay. Significant nitrate loss occurred in the outer Qinzhou Bay, which was related to the intense hydrodynamic condition. Moreover, phytoplankton assimilation mainly utilized NH4+ due to sufficient NH4+ in the outer Qinzhou Bay. In contrast, nitrate loss was also found in the outer Tieshangang Bay, which is mainly related to the phytoplankton assimilation due to the weak hydrodynamic condition. In addition, the greater enrichment of δ18O−NO3− than δ15N−NO3− during both bays suggests that atmospheric deposition also contributes to the nitrate pool in the water and the impact of atmospheric deposition on the whole Beibu Gulf is relatively consistent. By this comparative study, we found that different nitrate biogeochemical processes occurred in these two types of bays, which were mainly determined by the difference of human activities and hydrodynamic conditions.